Balancing Communities, Cultures, and Conflict: Lessons Learned From the East Ramapo School District Legal Battle. (June 2016) - Ober, Patrick; Decker, Janet R.
This case illustrates why future school leaders must be prepared to handle complex legal and political issues that commonly arise in school districts today. We discuss a long-standing and unresolved legal battle between a Hasidic Jewish community and the public school district in East Ramapo, New York. In particular, we examine the difficulties educational leaders face when they must balance the needs of diverse groups within a school district. We conclude by analyzing the legal and political issues that arose in East Ramapo, including church–state separatism and special education. We also pose questions designed to prepare educational leaders for similar situations where they must address complex legal and political issues.